MENULIS SEBAGAI SALAH SATU UPAYA TERAPIS: STUDI KASUS PENANGANAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Adhani, Agnes (Widya Warta, 2012)
Language is a means of communication among the members of society. Language is realized in speech sounds produced by human organs of speech. Language function may be differentiated into four kinds, namely (1) as a means of self expressing, (2) as a means of communication, (3) as a means of social integrating and adapting, and (4) as a means of socialcontrolling. Besides, there are four language skills – listening, speaking, reading, and writing.To write, however, is a productive language skill using writings.To write is capable of opening a new horizon and expressing an apprehension. In addition, to write can also serve as a therapetic activity as well as a spiritual cure. Human beings as alter creators may make use of writing creatively. Therefore, writing may be used as a therapy to handle domestic violence victims.Domestic Violence (KDRT) is any act toward someone, especially a woman, of which may cause miseries or sufferings physically, sexually, and psychologially toward the victims.Moreover, the act intended may ruin a family, such as the act of threating to commit a coercion to seize one’s freedom illegally in a family. The act of writing which may be used to cure domestic violence victims, especially psychological violence victims, includes writing stories, letters, and diaries as a means of therapy for the victims.